PENINGKATAN KEMAMPUAN LITERASI BAHASA SISWA MELALUI PROGRAM 10 MENIT MEMBACA DI AWAL PEMBELAJARAN PADA KELAS II SD - Risa Rismawati; Ansar Ansar; Lia Nurhayati (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
The low language literacy skills of second-grade students at Muhammadiyah 1 Limboto Elementary School, characterized by a lack of reading fluency and comprehension of reading content, became the background of this study. The focus of the problem was directed at efforts to improve literacy through the implementation of a ten-minute reading program at the beginning of the lesson. This study used the Classroom Action Research model of Kemmis and McTaggart which was implemented in two cycles, including the planning, implementation, observation, and reflection stages of 28 research subjects. Data collection was carried out through activity observations, reading ability tests, and documentation studies. The research findings showed a significant increase in students' literacy competencies gradually. Quantitatively, in the first cycle, 21 students or 75% had achieved the success criteria, then this number increased drastically in the second cycle to 26 students or 93%. In addition to the numerical aspect, students also showed positive developments in pronunciation accuracy, intonation, and enthusiasm for independent reading that were more consistent compared to the initial conditions. The main conclusion confirms that the ten-minute reading program at the beginning of the lesson has proven to be very effective in boosting elementary school students' language literacy skills. This habituation strategy is able to build a culture of enjoyable literacy while strengthening the cognitive foundation of students in understanding text information critically and accurately for their academic success through an inclusive and well-planned education system. ABSTRAKRendahnya kemampuan literasi bahasa pada siswa kelas II SD Muhammadiyah 1 Limboto, yang ditandai dengan kurangnya kelancaran membaca dan pemahaman isi bacaan, menjadi latar belakang penelitian ini. Fokus masalah diarahkan pada upaya peningkatan literasi melalui penerapan program sepuluh menit membaca di awal pembelajaran. Penelitian ini menggunakan metode Penelitian Tindakan Kelas model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus, mencakup tahap perencanaan, pelaksanaan, observasi, serta refleksi terhadap 28 subjek penelitian. Pengumpulan data dilakukan melalui observasi aktivitas, tes kemampuan membaca, dan studi dokumentasi. Temuan penelitian menunjukkan peningkatan signifikan pada kompetensi literasi siswa secara bertahap. Secara kuantitatif, pada siklus I tercatat sebanyak 21 siswa atau 75% telah mencapai kriteria keberhasilan, kemudian angka tersebut meningkat drastis pada siklus II menjadi 26 siswa atau 93%. Selain aspek angka, siswa juga menunjukkan perkembangan positif dalam ketepatan lafal, intonasi, serta antusiasme membaca mandiri yang lebih konsisten dibandingkan kondisi awal. Simpulan utama menegaskan bahwa program sepuluh menit membaca di awal pembelajaran terbukti sangat efektif dalam mendongkrak kemampuan literasi bahasa siswa sekolah dasar. Strategi pembiasaan ini mampu membangun budaya literasi yang menyenangkan sekaligus memperkuat fondasi kognitif peserta didik dalam memahami informasi teks secara kritis dan akurat untuk keberhasilan akademik mereka melalui sistem pendidikan yang inklusif dan terencana baik.